A robust family of Golden Gate Agrobacterium vectors for plant synthetic biology - Emami, Shahram; Yee, Muh-ching; Dinneny, Jose R. (Frontiers in Plant Science, 2013)
Tools that allow for rapid, accurate and inexpensive assembly of multi-component combinatorial libraries of DNA for transformation into plants will accelerate the progress of synthetic biology research. Recent progress in molecular cloning methods has vastly expanded the repertoire with which plant biologists can engineer a transgene. Here we describe a new set of binary vectors for use in Agrobacterium-mediated plant transformation that utilizes the Golden-Gate cloning approach. Our optimized protocol facilitates the rapid and inexpensive generation of multi-component transgenes for later introduction into plants.